Phosphogypsum-based cementing material and preparation method thereof
By combining phosphogypsum, waste slag, fly ash and nanomodifiers, a new gelling material with high strength, fast hardening, good toughness and environmental protection characteristics was prepared, which solved the problem of difficulty in combining phosphogypsum with other industrial waste in the existing technology, and achieved the goal of efficient resource utilization of industrial waste and low-carbon environmental protection of building materials.
Patent Information
- Application Number
- CN202411796654.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-21
AI Technical Summary
The existing technology is difficult to effectively combine phosphogypsum with other industrial waste to achieve multiple performance improvements, and the production energy consumption of traditional building materials is high and environmental pollution is serious.
By mixing phosphogypsum, waste slag, fly ash and nanomodifier in specific proportions, pretreatment, grinding and heat treatment, a new gelling material with high strength, fast hardening, good toughness and environmental protection characteristics are prepared.
It realizes efficient resource utilization of industrial waste, reduces environmental pollution and land occupation, reduces production energy consumption, meets the demand for mechanical properties and construction efficiency in construction projects, and significantly improves the durability and multifunctional performance of materials.
Smart Images

Figure CN119661176A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a phosphogypsum-based cementitious material and a preparation method thereof. Background Art
[0002] With the acceleration of industrialization and urbanization, the generation and treatment of a large amount of industrial waste has become a global environmental and resource problem. Among them, phosphogypsum, as a by-product of the phosphorus chemical industry, produces about 4.5 to 5 tons of phosphogypsum for every ton of phosphoric acid produced. The storage and landfill methods not only occupy a large amount of land, but also may cause serious environmental pollution problems. According to statistics, the historical storage of phosphogypsum in my country has exceeded 1 billion tons, with an increase of more than 80 million tons each year. How to realize the resource utilization of phosphogypsum has become one of the hot issues in current research. On the other hand, the production of traditional building materials (such as cement) has high energy consumption and large carbon dioxide emissions, and the burden on the environment is increasing. In this context, the development of a new type of cementitious material based on industrial waste, low-carbon and environmentally friendly and excellent performance can not only reduce the use of traditional materials, but also promote the efficient utilization of industrial by-products, which meets the requirements of green buildings and circular economy.
[0003] Phosphogypsum is mainly composed of calcium sulfate dihydrate and has certain activity. It is a potential high-quality cementitious material raw material. However, untreated phosphogypsum has high water content and large particle size, and direct application will affect its reaction efficiency and performance. In addition, single phosphogypsum has a slow hardening speed and poor crack resistance, and its comprehensive performance needs to be improved through compounding with other materials and nano-modification.
[0004] Current research shows that industrial by-products such as waste slag and fly ash are rich in silicates and aluminates, which can significantly improve their strength and durability when used in combination with phosphogypsum. At the same time, the introduction of nanomaterials can optimize the microstructure of the material, enhance crack resistance and interface bonding performance. However, the existing technology is still insufficient in how to effectively combine phosphogypsum with other industrial wastes through reasonable proportions and optimized processes to achieve multiple performance improvements. Therefore, the development of a new type of cementitious material and its preparation method using phosphogypsum as the main raw material and combining waste slag, fly ash and nano-modifiers has important practical significance and application value. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a phosphogypsum-based cementitious material and a preparation method thereof, which solves the problems of land occupation and environmental pollution caused by traditional phosphogypsum treatment methods.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a phosphogypsum-based cementitious material, comprising the following component materials:
[0007] Phosphogypsum: 70% to 90%;
[0008] Waste slag: 1% to 15%;
[0009] Fly ash: 3% to 10%;
[0010] Nano modifier: 1% to 10%;
[0011] The phosphogypsum is pretreated to make its moisture content ≤5%, and its particle size distribution is adjusted to 3 μm to 5 μm within the D90 range.
[0012] Preferably, the nano-modifier includes but is not limited to a silane coupling agent, graphene oxide nanoparticles and a combination thereof.
[0013] Preferably, the waste slag is an industrial by-product and has a particle size of ≤10 μm.
[0014] Preferably, the fly ash is of grade 2 or above quality, and has a silicon content of ≥50%.
[0015] Preferably, the material is used in road paving, wall insulation and building concrete preparation.
[0016] A method for preparing phosphogypsum-based gelling agent comprises the following steps:
[0017] S1. Pretreatment of phosphogypsum: drying the phosphogypsum to reduce its moisture content to no more than 5%, and then grinding it;
[0018] S2. Raw material mixing: evenly mix the treated phosphogypsum, waste slag, fly ash and nano-modifier according to the corresponding allocated mass percentage;
[0019] S3, grinding treatment: grind the mixture to a fineness of 300m 2 / kg~500%m 2 / kg;
[0020] S4. Heat treatment: subjecting the mixture to a heat treatment at a temperature of 150°C to 200°C for 2h to 5h, to obtain a characteristic material with adjustable setting time and mechanical properties.
[0021] Preferably, in step S2, a small amount of water needs to be added during mixing to improve uniformity, and the water-to-material ratio is controlled between 0.2 and 0.4.
[0022] Preferably, in the step S3, 0.5% to 1% by weight of a dispersant is added during grinding, and the dispersant is selected from polycarboxylic acid or naphthalene-based high-efficiency dispersants.
[0023] Preferably, in the step S4, the initial setting time of the characteristic material is 50 min to 70 min, the final setting time is controlled within 5 h to 6 h, and the compressive strength is 43.5 MPa to 46 MPa.
[0024] Preferably, in the step S4, the atmosphere can be dynamically adjusted during the heat treatment process.
[0025] The present invention provides a phosphogypsum-based cementitious material and a preparation method thereof, which has the following beneficial effects:
[0026] 1. The present invention uses industrial wastes such as phosphogypsum, waste slag, and fly ash as main raw materials to achieve efficient resource utilization of solid wastes, reduce environmental pollution and land occupation problems caused by solid waste storage, and respond to the needs of circular economy and sustainable development. At the same time, the material preparation process has low energy consumption and less pollution, and meets green environmental protection requirements during production and use, providing a low-carbon and environmentally friendly solution for the construction industry.
[0027] 2. The cementitious material prepared by the present invention has both high strength and fast hardening characteristics, meeting the dual requirements of mechanical properties and construction efficiency in construction projects. The material also exhibits good durability, including water resistance, frost resistance and chemical corrosion resistance, and can adapt to various complex environmental conditions. Its multifunctional properties enable it to be widely used in various engineering scenarios such as road paving, wall insulation and building concrete preparation.
[0028] 3. The present invention significantly improves the microstructure of the material by introducing nano-modifiers, and enhances its density, crack resistance and toughness. The nano-modifiers not only promote the interfacial bonding between particles, but also enhance the overall strength and durability of the material, thereby achieving all-round optimization of material performance at the microscopic level. This improvement in structural performance forms a good synergistic effect with the realization of high strength and durability.
[0029] 4. The present invention utilizes industrial waste and a simplified preparation process, which greatly reduces production costs and improves the sustainability of materials. It has significant economic and social benefits and provides a feasible solution for the green transformation of the construction industry and the high-value utilization of industrial waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The figure is a flow chart of the method steps of the present invention. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Embodiment 1:
[0033] Please see attached Figure 1 The embodiment of the present invention provides a phosphogypsum-based cementitious material, comprising the following component materials:
[0034] Phosphogypsum: 70% to 90%;
[0035] Waste slag: 1% to 15%;
[0036] Fly ash: 3% to 10%;
[0037] Nano modifier: 1% to 10%;
[0038] The phosphogypsum is pretreated to make its moisture content ≤5%, and its particle size distribution is adjusted to 3μm to 5μm within the D90 range;
[0039] Nano-modifiers include, but are not limited to, silane coupling agents, graphene oxide nanoparticles, and combinations thereof;
[0040] Waste slag is an industrial by-product with a particle size of ≤10μm;
[0041] The fly ash shall be of grade 2 or above quality, with silicon content ≥50%;
[0042] The material is used in road paving, wall insulation and building concrete preparation.
[0043] Specifically, phosphogypsum is used as the main raw material, with a content of 70% to 90%. After drying, the moisture content is reduced to ≤5%, and the particle size is adjusted to 3μm to 5μm within the D90 range by grinding, which can effectively increase the specific surface area and reaction activity, thereby promoting hydration reaction and improving the strength and hardening performance of the material. Waste slag is an industrial by-product, with a content of 1% to 15% and a particle size of ≤10μm. It contains rich silicate and aluminate components and can react secondary with the hydration product of phosphogypsum under alkaline conditions to generate calcium sulfonate and CSH gel, which not only improves the early strength of the material, but also significantly enhances its density and durability. Fly ash is of secondary quality and above, with a content of 3% to 10%, and a silicon content of ≥50%. Its spherical particles improve the fluidity of the material and act as nucleation points to promote the generation of hydration products. At the same time, its filling effect can improve the density of the material, enhance crack resistance and durability. The content of nano-modifier is 1% to 10%, including but not limited to silane coupling agent and graphene oxide nanoparticles, wherein silane coupling agent can improve the strength and interface performance of materials through chemical bonding, and graphene oxide can improve the density and crack resistance of materials by optimizing microstructure, while improving thermal insulation performance. This material can be widely used in road paving, wall insulation and construction concrete preparation. Through the synergistic effect of multiple components, it has the advantages of high strength, fast hardening, good toughness and environmental protection, meeting the actual needs of engineering, and realizing the efficient resource utilization of industrial solid waste.
[0044] Embodiment 2:
[0045] A method for preparing phosphogypsum-based gelling agent comprises the following steps:
[0046] S1. Pretreatment of phosphogypsum: drying the phosphogypsum to reduce its moisture content to no more than 5%, and then grinding it;
[0047] S2. Raw material mixing: evenly mix the treated phosphogypsum, waste slag, fly ash and nano-modifier according to the corresponding allocated mass percentage;
[0048] S3, grinding treatment: grind the mixture to a fineness of 300m 2 / kg~500%m 2 / kg;
[0049] S4, heat treatment: heat treating the mixture at a temperature of 150°C to 200°C for 2h to 5h to obtain a characteristic material with adjustable setting time and mechanical properties;
[0050] In step S2, a small amount of water needs to be added to improve the uniformity of the mixture, and the water-to-material ratio is controlled between 0.2 and 0.4;
[0051] In step S3, 0.5% to 1% by weight of a dispersant is added during grinding, and the dispersant is selected from polycarboxylic acid or naphthalene-based high-efficiency dispersants;
[0052] In step S4, the initial setting time of the characteristic material is 50 min to 70 min, the final setting time is controlled at 5 h to 6 h, and the compressive strength is 43.5 MPa to 46 MPa;
[0053] In step S4, the atmosphere can be dynamically adjusted during the heat treatment process.
[0054] Specifically, in step S1, the focus is on reducing the moisture content by drying, controlling it to no more than 5%, and adjusting the particle size distribution in combination with grinding. By controlling the moisture content, the adverse effects of high moisture on the uniformity of the mixture and the grinding efficiency can be effectively avoided, while reducing the energy consumption of subsequent heat treatment. The grinding process increases the specific surface area and particle activity of phosphogypsum, provides a larger reaction contact area for subsequent chemical reactions, and improves the hardening performance and strength of the material.
[0055] In step S2, the treated phosphogypsum, waste slag, fly ash and nano-modifier are mixed in proportion, and a small amount of water is added to improve the uniformity of the mixture. The silicates and aluminates rich in waste slag and fly ash can produce secondary hydration reactions with phosphogypsum under alkaline conditions to generate calcium aluminate and other hydration products with enhanced structures. The addition of nano-modifiers can enhance the dispersibility of the mixture, optimize the microstructure of the material, and improve the strength, toughness and crack resistance of the cementitious material. Accurate control of the water-to-material ratio can avoid the decrease in workability caused by excessive water, while ensuring the uniformity of the mixture and the adequacy of subsequent reactions.
[0056] In step S3, after mixing, the materials are ground to a fineness of 300 m 2 / kg~500%m 2 / kg. The grinding fineness within this range can ensure the reactivity of the material, meet the needs of rapid hardening, and avoid excessive energy consumption and water absorption problems caused by over-grinding. Adding 0.5% to 1% by weight of a dispersant (such as polycarboxylic acid or naphthalene-based high-efficiency dispersants) can effectively reduce the agglomeration of particles, optimize the fluidity and dispersibility of the slurry, and at the same time improve the grinding efficiency and further improve the material properties;
[0057] In step S4, the mixture is heat treated between 150°C and 200°C for 2h to 5h to obtain a characteristic material with adjustable setting time and mechanical properties. During the heat treatment process, the formation of impurities and the occurrence of side reactions can be reduced by dynamically adjusting the atmosphere, thereby improving the purity and strength of the material. The appropriate heat treatment temperature can promote the formation of hydration reactions in the material and generate a stable crystalline structure. This heat treatment method can also accurately control the setting time, while significantly improving the compressive strength of the material to 43.5MPa to 46MPa, meeting the high performance requirements of engineering.
[0058] Example 3: Preparation and performance verification of cementitious materials based on phosphogypsum from different sources
[0059] step:
[0060] Raw materials preparation:
[0061] The phosphogypsum produced by four phosphorus chemical enterprises, namely Yichang Xingfa, Huanggang Xiangyun, Tongling Tonghua and Dazhou Wengfu, was selected as the main raw material.
[0062] The dihydrate gypsum content of each batch of phosphogypsum is above 90%, and the moisture content is 20% to 25%.
[0063] Phosphogypsum pretreatment:
[0064] Drying the phosphogypsum to reduce its moisture content to no more than 5%;
[0065] The phosphogypsum is refined using a grinding device until the particle size distribution is D90 in the range of 3-5 microns.
[0066] Mixing process:
[0067] Mix in the following proportions:
[0068] Phosphogypsum: 85%;
[0069] Fly ash: 3%;
[0070] Waste slag: 2%;
[0071] Nano modifier: 9%.
[0072] The above materials were mixed using a ball mill and dry-milled for 30 minutes to ensure that all components were fully blended.
[0073] Heat Treatment:
[0074] The mixture is placed in a high temperature furnace for heat treatment, and the specific conditions are as follows:
[0075] Temperature: 180℃;
[0076] Duration: 3 hours.
[0077] Performance test data:
[0078]
[0079]
[0080] Summarize:
[0081] Consistency: This example shows that the performance of the cementitious materials prepared from phosphogypsum from different sources under the same proportion and process conditions is basically consistent, with high repeatability and stability.
[0082] Excellent performance: The compressive strength is higher than 43MPa, and the setting time is moderate (initial setting 1 hour, final setting 6 hours), which meets the needs of construction.
[0083] Environmental protection and resource utilization: This process makes full use of industrial by-products such as phosphogypsum, waste slag and fly ash, effectively realizes the resource utilization of solid waste, and demonstrates excellent environmental benefits and economic value.
[0084] This example verifies the high stability and applicability of cementitious materials under conditions of phosphogypsum from different sources, providing reliable data support for industrial promotion.
[0085] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A phosphogypsum-based cementitious material, characterized in that: Includes the following components: Phosphogypsum: 70% to 90%; Waste slag: 1% to 15%; Fly ash: 3% to 10%; Nano modifier: 1% to 10%; The phosphogypsum is pretreated to make its moisture content ≤5%, and its particle size distribution is adjusted to 3 μm to 5 μm within the D90 range.
2. A phosphogypsum-based cementitious material according to claim 1, characterized in that: The nano-modifier includes but is not limited to a silane coupling agent, graphene oxide nanoparticles and a combination thereof.
3. The phosphogypsum-based cementitious material according to claim 1, characterized in that: The waste slag is an industrial by-product, and its particle size is ≤10 μm.
4. The phosphogypsum-based cementitious material according to claim 1, characterized in that: The fly ash is of grade 2 or above quality, and has a silicon content of ≥50%.
5. The phosphogypsum-based cementitious material according to claim 1, characterized in that: The material is used in road paving, wall insulation and building concrete preparation.
6. A method for preparing phosphogypsum-based cementitious material, according to a phosphogypsum-based cementitious material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Pretreatment of phosphogypsum: drying the phosphogypsum to reduce its moisture content to no more than 5%, and then grinding it; S2. Raw material mixing: evenly mix the treated phosphogypsum, waste slag, fly ash and nano-modifier according to the corresponding allocated mass percentage; S3, grinding treatment: grind the mixture to a fineness of 300m 2 / kg~500%m 2 / kg; S4. Heat treatment: subjecting the mixture to a heat treatment at a temperature of 150° C. to 200° C. for 2 h to 5 h, to obtain a characteristic material with adjustable setting time and mechanical properties.
7. A method for preparing phosphogypsum-based gelling agent according to claim 6, characterized in that: In the step S2, a small amount of water needs to be added during mixing to improve uniformity, and the water-to-material ratio is controlled between 0.2 and 0.
4.
8. A method for preparing phosphogypsum-based gelling agent according to claim 6, characterized in that: In the step S3, 0.5% to 1% by weight of a dispersant needs to be added during grinding, and the dispersant is selected from polycarboxylic acid or naphthalene-based high-efficiency dispersants.
9. A method for preparing phosphogypsum-based gelling agent according to claim 6, characterized in that: In the step S4, the initial setting time of the characteristic material is 50 min to 70 min, the final setting time is controlled at 5 h to 6 h, and the compressive strength is 43.5 MPa to 46 MPa.
10. A method for preparing phosphogypsum-based gelling agent according to claim 6, characterized in that: In the step S4, the atmosphere during the heat treatment can be dynamically adjusted.
Citation Information
Cited By
Preparation and resource utilization method of aerogel thermal insulation material based on ardealite slag solid waste
CN120841927A